The influence of gastric digestion on the development of food allergy - Untersmayr, Eva (Rev Fr Allergol (2009), 2015)
Food allergy represents an increasing health concern worldwide. To identify mechanisms and risk factors associated with food allergy development major research efforts are ongoing. For a long time only food allergens that are resistant to gastric enzymes were accepted to harbor sensitizing capacity via the oral route. However, over the past years several studies reported that even important food allergens can be readily degraded by digestive enzymes. Interestingly, a number of in vitro experiments confirmed that impairment of physiological gastric digestion by elevating gastric pH levels was associated with protein resistance. Additionally, pharmacological gastric acid suppression was found to be a risk factor for food allergy induction. In contrast, protein modifications resulting in increased susceptibility to digestive enzymes were reported to decrease the sensitization capacity via the oral route. The here reviewed data highlight the important gate keeping function of physiological gastric digestion in food allergy.